2011
DOI: 10.1111/j.1447-0756.2011.01562.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipids level assessed in early pregnancy and risk of pre‐eclampsia

Abstract: Early pregnancy dyslipidemia, particularly hypertriglyceridemia appears associated with increased risk of pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
3
11
1
10
Order By: Relevance
“…Increased glycerol was detected in the women with PE, similar to the Bahado-Singh study [26], where it was attributed to abnormal lipid metabolism as it forms the backbone of triglycerides. The lipoprotein profiles here shown related to PE are similar to those found for people at risk of CVD [28], with increased low density lipoprotein levels. Lipid dysfunction starts early in pregnancies destined for PE development [28], suggesting that metabolomics may be used to predict the onset of PE.…”
Section: Discussionsupporting
confidence: 75%
“…Increased glycerol was detected in the women with PE, similar to the Bahado-Singh study [26], where it was attributed to abnormal lipid metabolism as it forms the backbone of triglycerides. The lipoprotein profiles here shown related to PE are similar to those found for people at risk of CVD [28], with increased low density lipoprotein levels. Lipid dysfunction starts early in pregnancies destined for PE development [28], suggesting that metabolomics may be used to predict the onset of PE.…”
Section: Discussionsupporting
confidence: 75%
“…Clinical studies have found that patients with preeclampsia, especially early-onset preeclampsia, had existing abnormal lipid metabolism, involving FFAs [20], triglycerides [21,22], cholesterol [23], low-density lipoprotein [24] and phospholipids [25]. FFAs are not only used as mitochondrial substrates for FAO to supply energy, they also have a role in oxidative stress and inflammatory signalling pathways; this role has had much attention during research into the pathogenesis of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…De la dislipidemia observada en el embarazo, la hipertrigliceridemia se ha descrito como parte de la etiopatogenia y como predictor del riesgo de preeclampsia 13,15,[20][21][22][23] . En este sentido, aunque los triglicéridos pueden estar elevados en las gestaciones normales, un incremento excesivo puede conducir a un entorno oxidativo con lesión endotelial y desarrollo consiguiente de preeclampsia 18 .…”
Section: Figuraunclassified
“…Es de destacar que la asociación de triglicéridos elevados (> 181 mg/dl) y concentraciones elevadas de LDL oxidado aumentaban el riesgo de preeclampsia en casi 9 veces (OR: 8,9; IC 95%: 3,1-26,2) 21 . Si bien en la mayoría de estos estudios las muestras sanguíneas se obtuvieron en el tercer trimestre del embarazo, también se han encontrado concentraciones de triglicéridos superiores en la preeclampsia, cuando estas se determinan antes de las 20 semanas de gestación 18,23,24 .…”
Section: Figuraunclassified
See 1 more Smart Citation